Varus knee deformity in adolescent soccer players - Krajnc, Zmago; Vogrin, Matjaž (Acta Medico-Biotechnica, 2021)
The lower limb axis develops dynamically throughout the first and second decades of life. In recent years, with respect to youth athletes, we have been facing a progressive increase in the intensity of exercise during training and competition (involving increased time, frequency, and power), and, as a result, there has been an increase in the number of acute and chronic overuse injuries. There are some sports with a higher incidence of injuries, one of which is soccer. A review of literature for the past 15 years with a focus on varus knee deformities in adolescent soccer players showed that varus axial deformities of the lower limbs occur more frequently in soccer players than in the general population and in athletes from other sport, probably due to the specific loading pattern in soccer training. Varus deformities alter knee biomechanics, which results in medial joint space overloading, and consequently an early onset of degenerative joint disease. In addition, bowlegs predisposes athletes to patellofemoral pain syndrome and meniscal lesions. The etiology of genu varum in soccer is thought to be multifactorial, ranging from the natural selection of players to mechanical overload of the proximal medial tibial growth plate. A growing number of clinical reports and animal studies have indicated that intensive sport training may precipitate pathologic changes of the knee joint growth plate, and even produce a growth disturbance.